Triatomines (Hemiptera, Reduviidae) prevalent in the northwest of Peru: species with epidemiological vectorial capacity - Cuba, César Augusto Cuba (2007)
ABSTRACT: The development of strategies for the adequate control of the vector transmission of Chagas disease depends on the availability of updated data on the triatomine species present in each region, their geographical distribution, natural infections by Trypanosoma cruzi and/or T. rangeli, eco-biological characteristics and synanthropic behavioral tendencies. This paper summarizes and updates current information, available in previously published reports and obtained by the authors our own field and laboratory studies, mainly in northwest of Peru. Three triatomine species exhibit a strong synanthropic behavior and vector capacity, being present in domestic and peridomestic environments, sometimes showing high infestation rates: Rhodnius ecuadoriensis, Panstrongylus herreri and Triatoma carrioni The three species should be given continuous attention by Peruvian public health authorities. P. chinai and P. rufotuberculatus are bugs with increasing potential in their role as vectors according to their demonstrated synanthropic tendency, wide distribution and trophic eclecticism. Thus far we do not have a scientific explanation for the apparent absence ofT. dimidiata from previously reported geographic distributions in Peru. It is recommended, in the Peruvian northeastern Amazon region, the development of field studies on species of the genus Rhodnius, as well as of other triatominae, to evaluate their present Trypanosomatidae vector capacity. _______________________________________________________________________________________ RESUMEN